Six-degree-of-freedom magnetic actuation for wireless microrobotics. (January 2016) - Diller, Eric; Giltinan, Joshua; Lum, Guo Zhan; Ye, Zhou; Sitti, Metin
Existing remotely actuated magnetic microrobots exhibit a maximum of only five-degree-of-freedom (DOF) actuation, as creation of a driving torque about the microrobot magnetization axis is not achievable. This lack of full orientation control limits the effectiveness of existing microrobots for precision tasks of object manipulation and orientation for advanced medical, biological and micromanufacturing applications. This paper presents a magnetic actuation method that allows remotely powered microrobots to achieve full six-DOF actuation by considering the case of a non-uniform magnetization profile within the microrobot body. This non-uniform magnetization allows for additional rigid-body torques to be induced from magnetic forces via a moment arm. A general analytical model presents the working principle for continuous and discrete magnetization profiles, which is applied to permanent or non-permanent (soft) magnet bodies. Several discrete-magnetization designs are also presented which possess reduced coupling between magnetic forces and induced rigid-body torques. Design guidelines are introduced which can be followed to ensure that a magnetic microrobot design is capable of six-DOF actuation. A simple permanent-magnet prototype is fabricated and used to quantitatively demonstrate the accuracy of the analytical model in a constrained-DOF environment and qualitatively for free motion in a viscous liquid three-dimensional environment. Results show that desired forces and torques can be created with high precision and limited parasitic actuation, allowing for full six-DOF actuation using limited feedback control.